Effectiveness of Animated Spokes-Character in Advertising Targeted to Kids - Komal Shuja; Mazhar Ali; Munazzah Mehak Anjum; Abdul Rahim (Journal of Marketing Management and Consumer Behavior, 2018)
The purpose of this study is to find the effectiveness of using animated characters in advertising targeted to kids. The research design is quantitative and its research type is causal. The respondents of the study are `Pre-primary school going kids' from nine different schools belonging to different areas of Karachi, Pakistan. Data is analyzed through Classification Regression Tree (CART). The findings of this research study reveal that liking of the animated spokes character has a significant effect on product and brand character recognition, Product-Brand Character Association and brand preference. The majority of earlier related studies have been descriptive in nature. This study has used relatively advanced measurement technique like CART thereby making a methodical contribution. It is especially useful considering the paucity of research studies on advertising targeted at kids in Pakistan.
https://journal-of-marketing-management-and-consumer-behavior.com/index.php/JMMCB/article/view/74
Keywords: M37; 330; Children Buying Behavior; Animated Character; Advertising Effectiveness; Brand Recall; Brand Recognition; Brand Preference; Brand Association